EFFECTS OF NUTRITION AND PARENTING STYLE ON CHILD DEVELOPMENT AT THE AGE OF 3-5 YEARS - Aprillia Ayu SY et al (Baqai Journal of Health Sciences)
Child development is basically the changes that occur in children from various aspects. The development is influenced by both internal factors (such as genetics and hormonal) as well as environmental and parental stimulation as an external factor. The objective of this study was to determine the effects of nutrition and parenting style on child development in Wilayah Puskesmas Social District of Palembang. The study included 107 children of age 35 years. The children were selected with purposive sampling technique using simple random sampling method and the data was analyzed statistically. The results of the study indicated that there is an influence of parenting style towards child development whereas there is no influence of nutritional status on child development. The study concluded that non-authoritative parenting style may lead to doubting the development of a child six times greater than the authoritative parenting style